Pengaruh Gaya Kepemimpinan Transformasional, Motivasi, Lingkungan Kerja Non Fisik, dan Kompensasi Non Finansial terhadap Loyalitas Karyawan - Radani, Abrar Syarom; Suyoto, Suyoto; Purnadi, Purnadi; Randikaparsa, Irawan (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study is to examine the influence of Transformational Leadership Style, Motivation, Non-Physical Work Environment, and Non-Financial Compensation on employee loyalty. This research employs a quantitative approach with a random sampling technique involving 107 employees. Data were collected through the distribution of questionnaires using a 5-point Likert scale and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to test the relationships between variables. The results show that Transformational Leadership Style and Non-Financial Compensation do not have a significant effect on employee loyalty. Meanwhile, Motivation and Non-Physical Work Environment have a positive and significant influence on employee loyalty. These findings highlight the importance of providing motivation to employees and creating a supportive non-physical work environment to foster and enhance employee loyalty within the company. This study also affirms the relevance of social exchange theory in explaining how non-material interactions in the workplace can play a crucial role in building long-term employee commitment to the organization.